Analisis Semiotika Roland Barthes dan Nilai Moral pada Film Second Miracle in Cell Number Seven Karya Herwin Novianto serta Pemanfaatannya sebagai Bahan Ajar Sastra di Sekolah Menengah Atas - Nia Fadilla Agustin; Sopyan Sauri; Purlilaiceu Purlilaiceu (Jurnal Bahastra, 2026)
This study is situated within the growing need to integrate film-based media into literary learning by examining how semiotic signs and moral values are represented and pedagogically utilized. It addresses the research problem of how Roland Barthes’ semiotic elements—denotation, connotation, and myth—along with moral values are constructed in the film 2nd Miracle in Cell No. 7 by Herwin Novianto and how these elements can be applied as teaching materials in senior high school. Employing a qualitative approach with a descriptive method, the study analyzes scenes and dialogues through observation and documentation techniques, using Barthes’ semiotic framework and Wicaksono’s moral value categories, including human relations with God, self, others, and the universe. Data were analyzed through reduction, display, and conclusion drawing. The findings reveal that the film presents layered meanings through semiotic structures and conveys diverse moral values that are relevant to students’ social and emotional development. The study argues that these findings support the use of the film as an effective and contextual teaching resource for Grade XI students, particularly in learning critical response texts, as it enhances interpretive skills and moral awareness.